Pengaruh Pupuk Majemuk NPK dan Fosfat terhadap Pertumbuhan dan Produksi Jarak Pagar IP3-P - Kurnia Dewi Sasmita; Dibyo Pranowo (Jurnal Tanaman Industri dan Penyegar, 2011)
Jatropha curcas was one of raw alternative material to produce bio fuel. Production of Jatropha require fertilizers in order to optimalize input usage. This research to determine dose of NPK (15:15:15) and fosfat fertilizers for growth and production of Jatropha curcas L provenan IP3-P. The research was conducted at Jatropa curcas main garden, Pakuwon, Sukabumi in March to December 2009. The design environment used Random Block Design (RBD)  arranged in factorial and repeated 3 replications. The first factor was dose of NPK fertilizers i.e : 0, 60, 120, 240, 360 g/tree/year, and comparator dose 40 g urea/tree/year, 110 g SP-36/tree/year, 30 g KCl/tree/year. Second factor was dose of P fertilizers i. e. : 0, 10, 17, 24 g P/tree/year. The result showed that 360 g NPK fertilizers/tree/years application significantly increases vegetative growth on number of branch and diameters of stem. The best dose of fosfat fertilizer for vegetative growth was 17 g/tree/year. Combination of NPK fertilizers with dose 240 g/tree/year and 17 g P fertilizer/tree/year increases significantly wight of fresh fruit and wight of dry fruit at 6 month of tree age.